Comparison of two texts from the Peruvian oral tradition with textual genetics - LaMadrid-Vivar, Pablo L. (2022)
The objective of this article is to compare two texts of the Peruvian oral tradition, the stories "El caldo de sapo" and "El condemned de Vicco", narratives belonging to the province of Pasco, for which both texts were analyzed with genetics or textual criticism. . The analysis compared the antetexts with the texts; the antetexts as original stories of the oral narration and the texts as written stories with improvements made by the transcribers. The method used in the investigation was the use of recursion and hermeneutics, methodological procedures of textual criticism, for which the original essence of the antetexts and their variation when they became texts were analyzed and interpreted. The main result obtained in the comparison shows that the versions of the antexts constitute the fundamental support for the edition of the official texts that will later be disseminated to the public for their knowledge and reading. It was concluded that without antetexts there are no texts, since men dedicated to writing first prepare their drafts to publish the final versions. Textual genetics makes it possible to compare antetexts and texts as a process of textual elaboration and re-elaboration, and thus lead to the authenticity of the text.